Association of Serum Lactic Dehydrogenase Level with Severity of Preeclampsia - Parvin, Salma; Hoque, Humaira; Walida, Salma Akhtar; Banu, Shabnam (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: : The present study was undertaken to measure the levels of lactic dehydrogenase (LDH) in normal pregnancy, mild preeclampsia and severe preeclampsia and compare them among the three groups of women. Methods: This cross-sectional analytical study was carried out in the Department of Obstetrics & Gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, between January 2014 to December 2014. A total of 120 pregnant women admitted in the above-mentioned hospital were included in the study. Pregnant women with blood pressure ≥140/90 mmHg and proteinuria ≥ 0.3 gm/24 hours were included in the study as case, while pregnant women with normal blood pressure without proteinuria were included as control. Of them 40 women were mildly preeclamptic, 40 severely preeclamptic and 40 were normal pregnant women. While preeclampsia was exposure variable, the outcome variable was LDH level. Lactic Dehydrogenase (LDH) level was measured in all the study subjects. Pregnant women with diabetes, chronic renal disease, hepatic disease, systemic infection and systemic lupus erythematosus, cardiovascular disease, essential hypertension, thyroid disorder and hemorrhagic disorders were excluded. Result: The case and control groups were almost similar with respect to age with mean age of the cases and controls being 26.1 and 27.2 years respectively (p = 0.272). However, preeclamptic patients were comparatively heavy than the normal pregnant women (31.4 ± 7.5 vs. 26.3 ± 3.1 kg/m2) (p = 0.001). The preeclamptic women exhibited significantly raised serum LDH level than their normal counterparts did (561.4 ± 301.2 vs. 270.2 ± 89.3 U/L, p = 0.001). More than half (52.5%) of the severe preeclamptic women had LDH ≥ 600 U/L as opposed to only 17.5% of the mild preeclamptic patients with risk of having raised LDH in severe preeclamptic patients being > 5-fold (95% CI of OR = 1.8 – 14.5) higher than that in the mild preeclamptic patients (p = 0.001). The LDH level was also found to increase with increasing severity of preeclampsia (p < 0.001). Both systolic and diastolic blood pressures of mild and severe preeclamptic patients had significantly linear correlations with serum LDH levels. Proteinuria in preeclamptic patients were also significantly correlated with LDH level (r = 0.636, p = 0.001). Categorically both systolic and diastolic blood pressures in severe form of preeclampsia were associated with higher level of LDH (> 800 U/L) (p = 0.003 and p = 0.012 respectively). Conclusion: The study concluded that LDH level increases in preeclampsia patients and rise of serum LDH is associated with severity of preeclampsia. Ibrahim Card Med J 2022; 12 (1): 46-51